Potentiometric Determination of Ketotifen Fumarate in Pharmaceutical Preparations and Urine Using Carbon Paste and PVC Membrane Selective Electrodes. (13th October 2011) - Frag, Eman Y. Z.; Mohamed, Gehad G.; Khalil, Mohamed M.; Hwehy, Mohammad M. A.
Abstract : This study compares between unmodified carbon paste (CPE; the paste has no ion pair) and polyvinyl chloride (PVC) membrane selective electrodes that were used in potentiometric determination of ketotifen fumarate (KTF), where sodium tetraphenylborate (NaTPB) was used as titrant. The performance characteristics of these sensors were evaluated according to IUPAC recommendations which reveal a fast, stable, and linear response for KTF over the concentration range of 10 −7 to 10 −2  mol L −1 . The electrodes show Nernstian slope value of52.51 ± 0.20 and51.51 ± 0.25  mV decade −1 for CPE and PVC membrane electrodes at 30 ∘ C, respectively. The potential is nearly stable over the pH range 3.0–6.0 and 2.0–7.0 for CPE and PVC membrane electrodes, respectively. Selectivity coefficient values towards different inorganic cations, sugars, and amino acids reflect high selectivity of the prepared electrodes. The electrodes responses at different temperatures were also studied, and long operational lifetime of 12 and 5 weeks for CPE and PVC membrane electrodes, respectively, were found. These are used for determination of ketotifen fumarate using potentiometric titration, calibration, and standard addition methods in pure samples, its pharmaceutical preparations (Zaditen tablets), and biological fluid (urine). The direct potentiometric determination of KTF using the proposed sensors gave recoveries % of98.97 ± 0.53 and98.62 ± 0.74 with RSD 1.42 and 0.63% for CPE and PVC membrane selective electrodes, respectively. Validation of the method shows suitability of the proposed sensors for use in quality control assessment of KTF. The obtained results were in a good agreement with those obtained using the reported spectrophotometric method.